In Silico Testing of the Semi-Closed Loop Infusion System with a New Simulator - Markevicius, V.; Andrijauskas, A.; Navikas, D.; Dubauskiene, N.; Porvaneckas, N.; Stankevicius, E.; Uvarovas, V.; Gelzinis, G.; Cepenas, M.; Andriukaitis, D.; Malekian, R. (Elektronika ir Elektrotechnika, 2014)
Goal directed fluid therapy (GDFT) implies the flow-related parameters guided infusion of fluids. It requires adherence to complex clinical algorithms and fluid protocols, as well as simultaneous monitoring of several parameters and evaluation of their fluid responsiveness or actual response to fluid challenges. Automated clinical decision support systems (ACDSS) are used to ease the task. However, they are based on the flow-related (hemodynamic) parameters – arterial blood pressure, cardiac output, etc. Meanwhile, infusions guided by hemodynamic endpoints may lead to edema. A mini Volume Loading Test (mVLT) may be helpful in detection of imminent edema from changes in hemodilution during stepwise infusion which is conventionally used for hemodynamic optimization. We developed an ACDSS which is based on evaluation of both hemodynamic and hemodilution parameters. It operates on the basis of our unique algorithm which implies interchangeable application of fluid loading, vasopressor injection and red cell transfusion. This ACDSS is used in our PC-based command centre of a prototype semi-closed loop (SCL) infusion system. We developed a simulator – ‘Virtual Patient’ – on the basis of our previous clinical records aiming to test a new controller, as well as train the research team before starting a clinical trial. In silico testing continued for 12 hours on five occasions. Primary endpoint was the compliance of a controller with our clinical algorithm and the stability of operation in a spectrum of arterial hypotension and bleeding scenarios. The prototype SCL infusion system was found ready for clinical validation. DOI: http://dx.doi.org/10.5755/j01.eee.20.9.8520